2018
DOI: 10.1073/pnas.1717070115
|View full text |Cite
|
Sign up to set email alerts
|

An atypical N-ethylmaleimide sensitive factor enables the viability of nematode-resistant Rhg1 soybeans

Abstract: N-ethylmaleimide sensitive factor (NSF) and α-soluble NSF attachment protein (α-SNAP) are essential eukaryotic housekeeping proteins that cooperatively function to sustain vesicular trafficking. The "resistance to 1" () locus of soybean () confers resistance to soybean cyst nematode, a highly damaging soybean pest. loci encode repeat copies of atypical α-SNAP proteins that are defective in promoting NSF function and are cytotoxic in certain contexts. Here, we discovered an unusual allele (-associated NSF on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
104
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 56 publications
(110 citation statements)
references
References 67 publications
(161 reference statements)
5
104
0
1
Order By: Relevance
“…Recently, Bayless et al . () reported ~300‐bp deletion within the promoter of another SNAP paralog gene ( Glyma.11G234500 ; α‐SNAP Ch11‐ IR) in ‘Forrest’ genotype. The authors cloned the WT locus of the GmSNAP11 from W82 with native promoter and terminator and observed elevated SNAP protein expression in transgenic roots.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, Bayless et al . () reported ~300‐bp deletion within the promoter of another SNAP paralog gene ( Glyma.11G234500 ; α‐SNAP Ch11‐ IR) in ‘Forrest’ genotype. The authors cloned the WT locus of the GmSNAP11 from W82 with native promoter and terminator and observed elevated SNAP protein expression in transgenic roots.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the interaction of two or more alleles (epistasis) plays a major role in an organism's resistance to diseases and pests (Bayless et al ., ; Meksem et al ., ; Nagel, ). The rhg1 GmSNAP18 protein interacts with NSF (N‐ethylmaleimide–sensitive factor) protein and disturbs vesicle trafficking (Bayless et al ., , ). We discovered that soybean germplasm provided a wide range of SCN resistance controlled by natural variants (SNP and CNV) at both the rhg1 and Rhg4 loci.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations